2012
DOI: 10.1093/ndt/gfs278
|View full text |Cite
|
Sign up to set email alerts
|

From preeclampsia to renal disease: a role of angiogenic factors and the renin-angiotensin aldosterone system?

Abstract: Complicating up to 8% of pregnancies, preeclampsia is the most common glomerular disease worldwide and remains a leading cause of infant and maternal morbidity and mortality. Although the exact pathogenesis of this syndrome of hypertension and proteinuria is still incomplete, a consistent line of evidence has identified an imbalance of proangiogenic and anti-angiogenic proteins as a key factor in the development of preeclampsia. Furthermore, more attention has been recently addressed to the renin-angiotensin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 60 publications
0
26
0
1
Order By: Relevance
“…A meta-analysis showed that the occurrence of micro-albuminuria is as high as 31 % in women with previous PE compared with 7 % in controls at a weighted mean of 7.1 years postpartum [2]. In addition, this study showed a graded relationship between microalbuminuria and the severity of PE, with a 4-fold increase after mild PE and a 8-fold increased after severe PE.…”
Section: Proteinuriamentioning
confidence: 54%
See 2 more Smart Citations
“…A meta-analysis showed that the occurrence of micro-albuminuria is as high as 31 % in women with previous PE compared with 7 % in controls at a weighted mean of 7.1 years postpartum [2]. In addition, this study showed a graded relationship between microalbuminuria and the severity of PE, with a 4-fold increase after mild PE and a 8-fold increased after severe PE.…”
Section: Proteinuriamentioning
confidence: 54%
“…In the meta-analysis of McDonald et al there were no significant differences in serum creatinine values, creatinine clearance and eGFR in formerly preeclamptic women compared with healthy parous controls [2] and Mangos et al [23] did not report eGFR changes 4-5 years postpartum. Only recently, subtle changes in renal function and renal haemodynamics in formerly preeclamptic women were reported.…”
Section: Kidney Function and Renal Haemodynamicsmentioning
confidence: 93%
See 1 more Smart Citation
“…In this regard, its definitions and the related uncertainties recall the discussion about the generic term of CKD [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Both conditions share frequent micro-vascular involvement, may be characterized by various combinations of hypertension and proteinuria, are related to pregnancy and one condition may mask or favour the development of the other [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this suggests that these women might have a higher risk for developing ESRD (33). The exact mechanisms underlying the increased risk for cardiovascular disease and ESRD in formerly preeclamptic women are not completely understood (30).…”
mentioning
confidence: 99%